Creation of a gamefish occurrence dataset from public-focused informational newsletters - Hedreen, Rebecca; Grace, Sean (2019 NEAFWA Conference, 2019)
Fish and wildlife agencies produce a bounty of information aimed at the public. Under the right circumstances, that information can be compiled into scientifically useful data to complement full scientific studies. This poster describes some preliminary results from a project to compile mentions of gamefish species, locations, and sizes throughout the Long Island Sound and surrounding waters from the Weekly Fishing Report (2006, 2008-2018) and the Trophy Fish Report (2009-2017), both produced by the Connecticut Dept. of Energy and Environmental Protection. The dataset consists of more than 20,000 entries from the reports collected weekly by DEEP employees from tackle shops and charter companies. The current portion of the analysis is to determine the characteristics of the dataset, such as entry types, species counts, and some general trends. Presented at the 2019 NEAFWA Conference in Groton, CT and the 2019 CSCU Faculty Research Conference at SCSU in New Haven, CT.
Keywords: Coastal fisheries; Connecticut; Data collections; Estuarine fisheries; Fish catch statistics; Game fish; Geographical coordinates; Geographical distribution; Life Sciences; Long Island Sound; Marine Biology; Sport fishing statistics; dept.bio; dept.lib

Feelings Translated by Wendeline Hardenberg - Le Hénand, Alice (Twirl Books, 2019)
It’s never too early to encourage children to talk about how they feel. This newest title in the Pull and …
Keywords: dept.lib

Who Lives Where? Translated by Wendeline Hardenberg - Babin, Stephanie (Twirl Books, 2019)
Sliding panels of animals near and far make for a delightful and satisfying format for matching game fun! Each of …
Keywords: dept.lib

Construction Translated by Wendeline Hardenberg - Babin, Stephanie (Twirl Books, 2019)
Bumpy roads, rough wood beams, and smooth concrete—there’s so much to discover in this Touch and ExploreTM book that’s all …
Keywords: dept.lib

Super Mazes in Space! Translated by Wendeline Hardenberg - Méhée, Loïc (Twirl Books, 2019)
Ten incredible mazes combine with a space adventure to provide a stellar game book for every puzzle-solving kid! Comics artist …
Keywords: dept.lib

Cars Translated by Wendeline Hardenberg - Krasinski, Geraldine (Twirl Books, 2019)
Turn a wheel to see cars of yesteryear, slide a new car onto a car carrier, pull a tab to …
Keywords: dept.lib

Yoga Together! Translated by Wendeline Hardenberg - Jouanne, Elisabeth (Twirl Books, 2019)
Keywords: dept.lib

Body Translated by Wendeline Hardenberg - Babin, Stephanie (Twirl Books, 2019)
Big, sturdy tabs to push and pull make for great learning fun in this brand-new nonfiction series. Preschool children learn …
Keywords: dept.lib

Baby Animals Translated by Wendeline Hardenberg - Babin, Stephanie (Twirl Books, 2019)
Keywords: dept.lib

Pirates Translated by Wendeline Hardenberg - Adams, Ines (Twirl Books, 2019)
Heave ho! Set sail on a high-seas adventure with swashbuckling pirates in search of treasure in this new Magnetology™ title. …
Keywords: dept.lib

Savanna Animals Translated by Wendeline Hardenberg - Dussaussois, Sophie (Twirl Books, 2019)
Take a trek into the wild . . . • Hunting for food • Building homes • Keeping cool • …
Keywords: dept.lib

Astronauts Translated by Wendeline Hardenberg - Dussaussois, Sophie (Twirl Books, 2019)
Count down to an incredible voyage! • Learning to pilot a spacecraft • Getting used to being weightless • Going …
Keywords: dept.lib

Jungle Animals Translated by Wendeline Hardenberg - Mazas, Marie (Twirl Books, 2019)
The shaggy fur of a sloth, the scaly skin of an iguana, and the rough hide of a tapir—there’s so …
Keywords: dept.lib

Bathtime Translated by Wendeline Hardenberg - Le Hénand, Alice (Twirl Books, 2019)
Little Crocodile, Little Monkey, and all their friends can think of a lot more things they’d rather do than take …
Keywords: dept.lib

Ultimate Book of Planet Earth Translated by Wendeline Hardenberg - Baumann, Anne-Sophie (Twirl Books, 2019)
The internationally successful Ultimate Book series expands its scope to embrace-very appropriately-the whole world! The Ultimate Book of Planet Earth …
Keywords: dept.lib

Badadoom Badabump! Translated by Wendeline Hardenberg - Baou, Bartélémi (Twirl Books, 2019)
Inspiring imagination and encouraging hours of creative play, Badaboom Badabump! is an innovative play set that not only includes a …
Keywords: dept.lib

Persephone 2014 Translated by Wendeline Hardenberg - Aubry, Gwenaëlle (Asymptote, 2019)
Keywords: dept.lib